Analysis of Factors Affecting Delays in Construction Projects in the Upstream Oil and Gas Industry of South Sumatra - Sonny Citra Permadi; I Putu Artama Wiguna (Eduvest - Journal of Universal Studies, 2025)
Upstream oil and gas construction projects in South Sumatra face significant challenges related to execution delays due to geographic, technical, and social complexities. This study aims to analyze the factors causing Project Delays and formulate context-specific mitigation strategies. The method employed is Partial Least Squares - Structural Equation Modeling (PLS-SEM), involving 186 respondents consisting of project owners and industry practitioners. The results indicate that the Material variable has the most significant direct impact on Project Delays, followed by the Planning and Design variable. The Contractor factor acts as a mediator for the influence of the Labor, Financial and Economic, and External variables. Dominant delay-causing indicators include material shortages, inadequate site investigation, design mismatches, inaccurate price negotiations, and low safety awareness. The results of the Focus Group Discussion (FGD) support the quantitative findings by highlighting the importance of field data-based design validation, comprehensive site investigations, and the enhancement of local contractor capacity. The Focus Group Discussion also revealed that material unpreparedness and social conflicts arising from limited legal awareness and moral responsibility within local communities have further contributed to project delays. Based on these findings, the recommended strategies include conducting comprehensive site investigations based on subsurface, geotechnical, and social data, involving contractors from the early stages, implementing projects through digital approaches, and managing social risks through Corporate Social Responsibility (CSR) strategies and stakeholder engagement. This study offers practical contributions to improving the efficiency of upstream oil and gas projects, particularly in high-complexity regions such as South Sumatra.